The Canela m'ypé: 'mending ways' or modos de reparação, the splendour and misery (need there be?) of presenting new social categories through translation - Lillian DePaula; Márcio Filgueiras (JoSTrans: The Journal of Specialised Translation)
In this paper, the authors aim at explaining the different approaches used in the translation from English into Brazilian Portuguese of an anthropological work by William Crocker, who spent over 50 years studying the Canela tribe in northeastern Brazil. They focus on the concept-oriented, stereoscopic approach the translators used to take into account the sociological and anthropological underpinnings that contextualise both the original work and its translation. Inspired by Marilyn Gaddis Rose and Joshua M. Price, they explain their approach through an example of four concrete activities undertaken for the purpose of illustrating translation potentiality. Those activities were comprised of (1) comparing, contrasting, and reflecting on textuality and paratextuality through analysing, for instance, both book covers; (2) reflecting on translation specificity through a dialogue between Crocker and DePaula; (3) identifying social categories and how they were retained or not through the translation in terms of contextual settings; and (4) evaluating procedures to introduce new conceptual understandings through the analysis of the anthropologist's notes, footnotes and so forth. The paper aims to illustrate concretely how interlingual, intralingual and extralingual transfer constraints can all shape not only the end result (the translation product itself), but also the process of translation.